Analisis Kesulitan Pembelajaran Hiwar Bahasa Arab pada Siswa SMP TMI Raudlatul Qur’an Metro - Anisa Amalia Hazrah; Ahnaf fauzi; Rangga Ferialdo Aulia S; Sayidil Hanief (Institut Muslim Cendekia, 2026)
Hiwar learning is an important aspect of Arabic language instruction aimed at developing students’ speaking skills. However, its implementation continues to face various challenges that affect students’ ability to communicate in Arabic. This study aims to analyze the difficulties encountered in learning Arabic hiwar among junior high school students, identify the contributing factors, and describe the intervention efforts implemented within the Islamic boarding school environment. This research employed a qualitative approach with a field research design. Data were collected through observation, semi-structured interviews, and documentation involving Arabic language teachers and students of Class VIII E at TMI Raudlatul Qur’an Metro Junior High School. Data were analyzed through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings reveal that difficulties in hiwar learning are influenced by the interaction of internal and external factors. The main finding indicates that students’ limited linguistic competence, particularly in vocabulary mastery and self-confidence, is exacerbated by learning conditions within the Islamic boarding school, including limited instructional time, dense student activities, and less-than-optimal learning strategies and media. To address these challenges, teachers implemented several intervention efforts, including vocabulary reinforcement, guided hiwar practice, academic tutoring, and motivational support to enhance students’ participation and Arabic-speaking proficiency.